Terapi Menulis untuk Meningkatkan Kemampuan Kognitif Pecandu Narkoba di Lapas Dewasa Kota Blitar - Miza Rahmatika Aini; Hesty Puspitasari (ALFABETA: Jurnal Bahasa, Sastra, dan Pembelajarannya, 2021)
Drugs is the term for narcotics, psychotropic substances and other dangerous. The term often used is DRUGS (Narcotics, Alcohol, Psychotropics and other addictive substances) Around us today, there are a lot of addictive substances that are negative and very harmful to the body. Known as narcotics and illegal drugs. In this sophisticated modern era, drugs have become a problem for mankind in various parts of the world. Drugs that can destroy bright reasoning destroy body and soul, inevitably can threaten the future of mankind. In life, a critical step of the neurodevelopmental process, drug abuse may be caused brain plasticity mechanisms that can induce long-lasting improvements in neural circuits and in the end, actions. One of the effects of these improvements is the disability. Cognitive functions, with negative academic effects on the acquisition of new information. Knowing those phenomena, the researcher had alternative therapy for increasing their cognitive functions. The researcher used writing as a therapy for them. The advantages of writing are immense, but they are also underestimated. Writing has profound therapeutic benefits. Writing is also a healthy brain exercise to activate brain cells and boost memory. This research conducted in Adult Prison in Blitar city, in which 15 drug prisoners were treated into writing theraphy. The result is they could write as well as the icreasing of their cognition.